System efficiency of heat integrated H2-fueled PEMFC power generation on cruise ships. An evaluation of heat and power system layouts on a modern passenger carrying vessel - Lidqvist, Jesper (My University, 2023)
With the drive to decarbonize the majority of transport sectors, the shipping indus try has developed a selection of different concepts to lower the emissions of different ship-types. Different fuel in form of e-fuels, bio-fuels and gaseous fuels like hydrogen and natural gas are promising developments. With the change of fuel types different power conversion technologies comes in to question, with the fuel cell being of inter est thanks to it’s high efficiency and in the case of the PEM type fuel cell powered by hydrogen, no emissions while producing power. This work evaluates the implementation of a hydrogen fueled PEM fuel cell power system onboard a cruise ship, describing the original studied ships system and the parameters that governs the fuel cells, modeling the use of the fuel cells to meet the power demand over several different case days in different setups, and testing several types of system to fulfill the heat demand of the vessel for the same cases. Also evaluating the effects of changed demand for heat and power, and resulting fuel consumption and efficiency of the different setups are presented and discussed. The amount of systems evaluated in this work limits the accuracy of the results, and is primarily used to evaluate different setups. The cases different power demand are extracted as 15-min average data, and thus lacks the accuracy to evaluate the demand response of the fuel cells in sub-minute scale. Higher efficiency were found where the load factors of the fuel cells were low, indi cating the potential of an oversized power generating system. The fuel cell capacity is however the main system cost driver, highlighting the sensitivity to system costs of fuel cells, and pointing to the trade-off that has to be made during design of a fuel cell powered vessel between efficiency and investment cost. The heat flows of the vessel are changed with the introduction of the low temperature waste heat expelled from the fuel cells, highlighting the need to move away from steam use onboard in favor of low temperature heat or electricity. The production of steam onboard can however be fulfilled with the use of hydrogen fired boilers, and can be combined with heat pumps and/or thermal energy storage.
Keywords: Fuel cell; Low temperature heat recovery; Maritime Hydrogen; Low carbon shipping; Ship energy systems